Identification of Potentially Diagnostic Leishmania braziliensis Antigens in Human Cutaneous Leishmaniasis by Immunoblot Analysis - Brito, Maria Edileuza F. (American Society for Microbiology, 2000)
The antibody response in patients with American cutaneous leishmaniasis was analyzed by immunoblotting with soluble and insoluble antigens of Leishmania braziliensis. The recognition of the 27- and/or 30-kDa soluble antigens was considered relevant for the diagnosis of cutaneous leishmaniasis. Immunoblotting was found to be significantly more sensitive and specific than indirect immunofluorescence and enzyme-linked immunosorbent assay.